Interlayer Spacing Regulation of Molybdenum Selenide Promotes Electrocatalytic Hydrogen Evolution in Alkaline Media. Issue 10 (24th August 2022) - Zhang, LiLi; Shen, Shijie; Zhang, Jitang; Lin, Zhiping; Wang, Zongpeng; Zhang, Qinghua; Zhong, Wenwu; Zhu, Liu; Wu, Guangfeng
Abstract: The construction of heterostructures is a versatile tactic to enhance catalytic activity. However, it is still elusive to realize the modulation of the interlayer spacing in this way to further improve the performance. Here, strong interfacial coupling between CoSe2 and MoSe2 by constructing CoSe2 /MoSe2 heterostructures is achieved. The interlayer spacing of MoSe2 is compressed by 0.3 Å. The enhanced charge transfer is validated by X‐ray absorption spectroscopy and X‐ray photoelectron spectroscopy. Coupled with the morphology of hollow microtubes, which can facilitate the exposure of active sites, CoSe2 /MoSe2 heterostructures reported here exhibit high activity (119 mV at 10 mA cm −2 ) and excellent stability with small degradation after 50 h operation, surpassing other analogous powdered electrocatalysts. This work sheds light on the importance of tuning the interlayer spacing to improve electrocatalytic activity. Abstract : The interlayer spacing of MoSe2 is compressed by 0.3 Å through constructing CoSe2 /MoSe2 heterostructures. Benefiting from the optimized electronic structure derived from interfacial charge transfer, and the rough morphology that fully exposes the active sites, the CoSe2 /MoSe2 heterostructures reported here shows the best hydrogen evolution reaction performance among related powdered electrocatalysts.